A comprehensive analysis of oxytocin: a potential brain-based treatment to regulate obesity - Alsayegh, Abdulrahman A.; Ashfaq, Fauzia; Bajahzer, Mohammed; Alshaharani, Mohammad Y; Almutairi, Ali Saad; Khan, Mohammad Idreesh; Alhomaid, Raghad M.; Beg, Mirza Masroor Ali (Frontiers in Endocrinology, 2026)
BackgroundGlobally, obesity is a serious health issue, and oxytocin may help regulate appetite and reduce food intake, particularly in obese individuals. One promising treatment option for controlling appetite and lowering food intake is oxytocin among the people living with obesity or overweight. Based on the relevant clinical studies, this systematic review article explored the role of oxytocin and its connection with obesity.MethodsThis review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines to ensure that our reporting was accurate and comprehensive. We examined 14 interventional studies (2015–2025) from PubMed, MEDLINE, and Scopus that had open full-text access using the keywords “Oxytocin”, “Obesity”, and “Oxytocin in Obesity”.ResultsOxytocin could be the treatment option for obesity and poor eating patterns, and it has been demonstrated that intranasal oxytocin administration reduces appetite and increases feelings of fullness, particularly in people with obesity. Administering a nasal spray of oxytocin (24 IU) can reduce appetite. Because it makes them feel fuller and less hungry, this is especially true for people with obesity. Additionally, oxytocin alters the way the brain functions in regions that govern reward and decision-making, which lessens food cravings, according to functional magnetic resonance imaging (fMRI). By influencing gut bacteria, it may also increase metabolism and assist people in controlling their eating habits. Oxytocin administration is associated with a significant reduction in weight and improved body composition. Additionally, it appears to have the potential to alleviate pregnancy related obesity. Although the initial findings are encouraging, more extensive research is necessary to confirm its effectiveness. Healthy eating and metabolism are associated with natural oxytocin levels, which suggests that it may be used to treat obesity.ConclusionOxytocin modulates appetite and brain reward pathways, offering a novel, brain-targeted approach to obesity treatment. Furthermore, clinical studies should explore long-term effects and optimal dosing to manage obesity.